A catalog of the types of Stratiomyidae, Tabanidae, Asilidae sensu lato, and Syrphidae (Insecta, Diptera) deposited in the Museo Argentino de Ciencias Naturales, Buenos Aires (MACN) With an appendix on types of Tabanidae deposited in the Instituto "Dr. Carlos G. Malbrán", Buenos Aires (ANLIS) - Bachmann, A.O. (2012)
The type specimens of all accepted categories of three names of Stratiomyidae, fifty-nine of Tabanidae, twenty-four of Asilidae sensu lato (includes Leptogastridae), and twenty of Syrphidae are recorded. In an appendix twelve paratypes of six species of Tabanidae are recorded, housed in the Administración Nacional de Laboratorios e Institutos de Salud "Dr. Carlos G. Malbrán" (ANLIS), Departamento Vectores, Buenos Aires.